Exploration and Identification of Arbuscular Mycorrhizal Fungi (FMA) in Sungkai Plants (Peronema canescens Jack) at Various Soil Depths - Rike Puspitasari Tamin; Suci Ratna Puri (Postgraduate, University of Mataram, 2024)
Sungkai (Peronema canescens Jack.) is one of the native species that can be developed in plantation forest development, where almost all soil types can be grown by sungkai because sungkai is one of the leading plant species. Therefore, it is necessary to carry out further sungkai cultivation activities to be developed and cultivated. The provision of FMA inoculation in plants to assist growth will be more optimal if using indigenous FMA spores (from the original plant stand). This research aims to explore and identify the types of Arbuscular Mycorrhizal Fungi found under Sungkai stands and analyze the effect of soil depth on the diversity and abundance of FMA spores under Sungkai stands. This research was conducted in sungkai stands with an area of 1.5 Ha by purposive sampling at a depth of 20-60 cm. Soil samples were taken from 5 points then composited and taken as much as 1 kg and inserted into an airtight plastic bag. The results of identification showed that there were 5 FMA genus in the Sungkai Planting Area, namely Glomus, Acaulospora, Entrospora, Gigaspora, and Scutellospora. The highest FMA spore density in each research location was found in the location at a depth of 20 cm with an average of 48 spores